FAITH TOURISM IN TAGAYTAY CITY: BASIS FOR DESTINATION MARKETING - Abad, Jamie S.; Alonsozana, Venicris M. (International Journal of Research -GRANTHAALAYAH, 2019)
A Faith Tourism tour package was proposed in one of the prominent cities in the Province of Cavite, Philippines based on Dr. Sampad Kumar Swain’s basic tour package components. Through Focus Group Discussion, document analysis and survey questionnaire, the study determined eight tour operators and their clients’ knowledge of Faith Tourism including its benefits and opportunities, and the skills and attitudes in making a Faith Tourism tour package. SWOT Analysis determined the marketing competitiveness of Tagaytay City through the World Economic Forum’s Tourism and Travel Competitive Index (TTCI) 2017. The millenial respondents of the survey questionnaire strongly agreed that the proposed faith tourism tour package is competitive and reflects Swain’s basic components. The common knowledge among tour operators regarding Faith Tourism is it is a pilgrimage, while the basic skills and attitude needed in making Faith Tourism itineraries are professionalism, knowledgeability, and patience. SWOT analysis as a tool for self-assessment revealed that Tagaytay City is “strongly” competitive based on the TTCI 2017 components.